FORMULASI SIRUP EKSTRAK DAUN SENDOK (Plantago mayor L.) SEBAGAI EKSPEKTORAN DENGAN PARAMETER UJI MUKOLITIK - Lutfiana Kusuma Wati (Fakultas Farmasi UMI, 2017)
Traditional medicines that derive from the plants processed in the form of traditional herb have provided a lot of contribution to the maintenance the health of community. Greater plantain (Plantago mayor L.) is one of natural materials that is useful as expectorant, however, so far the use is still processed traditionally by community.To find out and make sure that the ethanol extract of greater plantain (Plantago mayor L.) can be formulated to be syrup expectorant, then to determine the most effective concentration in lowering the viscosity of fluid mucus of every formula made.In this research, the syrup ethanol extract of greater plantain (Plantago mayor L.) was made with concentration variation of 6%, 8%, and 10%.Observation was made by looking at the lowering of viscosity of fluid mucus that has been diluted with phosphate buffer pH 7 by using viscometer Ostwald through the flow time. Based on the test result ANSIRA to 3 formulas of syrup expectorant and negative control, it was proved that the concentration of ethanol extract of greater plantain (Plantago mayor L.) in the treatment of this research significant effected in lowering the viscosity of mucus with price F count > F table or 66, 3181 > 4, 07 on the test level of 5% and 66, 3181 > 7, 59 on the test level of 1%. With the price KK 4, 11% then further test was done using BNJ test. Based on the test result BNJ, it was known the formula of syrup expectorant that most effective is the formula II with the concentration of ethanol extract of greater plantain 8%.